1988
DOI: 10.1016/0304-8853(88)90413-1
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering in heavy fermion compounds

Abstract: We present results of Raman spectroscopy and magnetic susceptibility measurements in the actinide compounds UO 2, UPt 3 and UBel3. The differences in the degree of localization of the 5f-electrons in the insulating UO 2 and in the metallic, heavy fermion compounds UPt 3 and UBel3 are discussed. In both types of compounds we find evidence of localized electronic excitations, which yield a good fit of the magnetic susceptibility data. The spin relaxation rates of UPt 3 and UBel3 at q --0 are determined experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Manara and Renker [21] measured the Raman spectra of a number of UO 2 /UO 2+x samples of differing stoichiometries and found that a peak around 1150 cm À1 was characteristic of stoichiometric UO 2 . This peak, also reported by Schoenes [33], Graves [28] and Blumenroeder et al [34], is attributed to a U 5 ? U 3 crystal field transition.…”
Section: Phonon Modesmentioning
confidence: 56%
“…Manara and Renker [21] measured the Raman spectra of a number of UO 2 /UO 2+x samples of differing stoichiometries and found that a peak around 1150 cm À1 was characteristic of stoichiometric UO 2 . This peak, also reported by Schoenes [33], Graves [28] and Blumenroeder et al [34], is attributed to a U 5 ? U 3 crystal field transition.…”
Section: Phonon Modesmentioning
confidence: 56%
“…44 This is at odds with both Raman results and calculations, but the reason for this is unclear. This assignment of the Raman band has persisted, 43,[48][49][50][51] primarily since its intensity increased with a temperature decrease (I 300 K E 0.25I 20 K ), 44,49 which is not expected for pure multiphonon excitation, but attributable to a band of electronic scattering origin. 49,52 This reasoning can be supported by single crystal measurements.…”
Section: Stoichiometric Uomentioning
confidence: 95%
“…As the materials under consideration do not contain any ferromagnetic components, the relative permeability is assumed to be : r = 1. The molar susceptibility of UO 2 , which is directly coupled to the relative permeability, has been investigated by Blumenröder et al [8] for a temperature range 30 K #T # 400 K. For the available data of this temperature range the assumption is valid. The relative permittivity was investigated by Hampton et al in 1985 [9] at room temperature.…”
Section: Materials Propertiesmentioning
confidence: 99%